"If I'm not gardening, I'm not at my happiest": exploring the positive subjective experiences derived from serious leisure gardening by older adults. Issue 4 (1st October 2016) - Cheng, Eva (Hui-Ping); Pegg, Shane
ABSTRACT: Exploring the indicators of an individual's happiness and well-being over their lifetime has become a major research focus. The aim of this study was to identify meanings and values of gardening as a core leisure activity in the lives of older individuals living in a community setting. A key focus of such effort being to discern whether or not leisure gardening contributes to the participants' overall level of happiness and subjective well-being. Participants were purposely selected from previous research conducted by the authors and who were identified as serious leisure gardeners. Semi-structured qualitative interviews were conducted with 13 Australians aged 57–84 years. Results identified that participants considered the activity as integral to who they were as a person. Moreover, the study found that the respondents considered gardening to be a central life interest that provided them with a social and active lifestyle. Critically, the activity also offered them a sense of accomplishment and satisfaction through which they derived a deep sense of enjoyment and happiness not experienced by them in other activities. Findings provide strong support for the activity of gardening to be considered more seriously by policy-makers and program developers as a core leisure pursuit that aids older adults to lead a more joyous and fulfilling life in their golden years.